A Comparative Study of K±/π± Ratio in Proton-Proton Collisions at Different Energies: Experimental Results versus Model Simulation. (17th January 2018) - Bhattacharyya, Swarnapratim; Haiduc, Maria; Neagu, Alina Tania; Firu, Elena
Abstract : A detailed study of energy dependence of K + / π +, K - / π - and total kaon to pion multiplicity ratio K + + K - / π + + π - = K / π has been carried out in proton-proton (pp) collisions at s = 6.3, 17.3, 62.4, 200, and 900 GeV and also at s = 2.7 6  TeV and 7 TeV in the framework of UrQMD and DPMJET III model. Dependence of K + / π + and K - / π - on energy shows different behavior for UrQMD and DPMJET III model. The presence of the horn-like structure in the variation of K + / π + and K - / π - with energy for the experimental data is supported by the DPMJET III model. Experimentally it has been observed that as energy increases, the total kaon to pion multiplicity ratio K + + K - / π + + π - = K / π increases systematically for pp collisions at lower energies and becomes independent of energy in LHC energy regime. Our analysis on total kaon to pion multiplicity ratio K + + K - / π + + π - = K / π with UrQMD data is well supported by the experimental results obtained by different collaborations in different times. In case of DPMJET III data, the saturation of K / π ratio at LHC region has not been observed.